Makna Frasa “ὁ ἀμνὸς τοῦ Θεοῦ” dalam Yohanes 1:29 - Lucas, Tjong Andrew; Binar, Sri (Jurnal Teologi dan Pelayanan Kerusso, 2024)
One of the theological titles addressed to Jesus Christ is the Lamb of God. This title can be found in John 1:29 and 1:36 which is the title of John the Baptist to Jesus,and is not found in the Synoptic Gospels. A number of scholars have attempted to interpret the phrase Lamb of God both in a literal and figurative sense and there are a number of different meanings. In this paper, the author seeks the meaning of the phrase Lamb of God in John 1:29 using the exegetical method. The exegetical method used three analyses: contextual analysis, historical, and grammatical and literal analysis. From the analysis carried out, it was found that the meaning of the phrase Lamb of God which is directed at Jesus explains the work of Jesus' salvation through His death on the cross which brought redemption and remission of sins for humans by taking Jewish background: the Passover lamb, and the divine qualities possessed by Christ as the Lamb of God.